Processing and marketing of rattan canes in Nepal - Chowdhary, C. L.; Dutta, I. C. (Banko Janakari, 2021)
This study highlights the processing and marketing of rattan canes with reference to small and medium enterprises (SMEs). The study was designed based on the exploratory research, and was carried out in all the districts of Nepal with rattan enterprises. The main objective was to assess the processing status, supply, and demand including constraints and potentialities of rattan-canes as well as their marketing practices. Systematic random sampling method was followed to take the sampling of rattan processing enterprises of CFUGs. The questionnaire survey was conducted among35 rattan entrepreneurs cum rattan traders and ten executive committee members of CFUGs. The quantitative data was analyzed using Frequency. The study found that hanger, cradle, stools, chairs, and tables were largely manufactured items among all the rattan-cane products. The annual consumption of imported rattan from India and other countries ranged from 850 MT to 1094 MT. Nepalese rattan fulfills 30% of the total demand. The average marketing margin of rattan products was found to be 37-64%. Nepalese rattan is potential to fulfill 70-80% of the total domestic demand of smaller size strands of rattan.